Paraguay Diagnostic Review of Consumer Protection and Financial Literacy : Volume 1. Key Findings and Recommendations - World Bank (World Bank Group, Washington, DC, 2015)
This review of the Consumer Protection and Financial Literacy Framework (CPFL) in Paraguay was undertaken in response to a request for technical assistance in this area made by the Central Bank of Paraguay (BCP). The objectives were: (i) to assess the existing consumer protection and financial literacy framework by reviewing laws, regulations, and actual practices in Paraguay, and comparing it with international good practice; and (ii) to provide recommendations on ways to improve the level of financial consumer protection and financial literacy in the country. The Diagnostic Review provides a detailed assessment of the institutional, legal and regulatory framework for consumer protection in four segments of the financial sector: (i) banks and finance companies, (ii) financial cooperatives, (iii) insurance companies, and, - in reflection of the important role they play in Paraguay - (iv) non-bank agents and mobile payment providers. Its findings and recommendations cover six thematic areas: (i) Institutional Arrangements, (ii) Legal and Regulatory Framework, (iii) Transparency and Disclosure, (iv) Business Practices, (v) Complaints Handling and Dispute Resolution, and as a stand-alone section (vi) Financial Education.